Kahoot: An Interactive Learning Tool for Enhancing Interest and Literacy Skills in Children Aged 5–6 Years - Maisari, Sri; Busri, Rahayu Vini (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
Children's interest in literacy is currently declining. This is evident in the low enthusiasm of young children when given books for learning to read, write, and count, compared to learning that is packaged using digital technology. Technology can be integrated as an attractive, interactive learning medium that is suitable for children's characteristics. Through the use of educational applications such as Kahoot, children can enjoy a new learning experience and atmosphere in literacy activities. The implementation of Kahoot requires teacher supervision. Children can use a single computer and projector, or each child can use their own digital device. Literacy for children aged 5-6 years encompasses understanding language, expressing language, literacy, and logical thinking. This research method is qualitative with a case study approach. The sampling technique used is purposive sampling, where the sample consists of children with low literacy interest and ability, totaling 15 children. The results of this study indicate changes in literacy interest and ability among children aged 5-6 years. In terms of interest, during learning activities using Kahoot, children are highly enthusiastic about learning letters and numbers, showing joy in learning to read, actively reading, and answering quizzes. In terms of literacy understanding, children can recognize patterns, ABCD–ABCD, arrange letters into words, write and read their own names, recognize sounds, identify familiar symbols, spell letters into words, identify groups of images with the same initial sound/letter, and understand the rules of the game.